Altruisme Efektif, Filantropi Islam, dan Kesejahteraan Publik: Sebuah Kritik - Anugrah , Iqra (Sodality: Jurnal Sosiologi Pedesaan, 2023)
Islamic philanthropy is often seen as a major articulation of Islamic principles of wealth redistribution and social justice, especially in rural and peripheral areas. In this mainstream narrative, the economic mandate of Islam is seen from a prism of noblesse oblige and/or reformism, turning the Islamic notion of solidarity into an individualized obligation for charity and almsgiving. This embourgeoisement of Islamic economic ethics overlaps with and embodies the idea of Effective Altruism (EA), a utilitarian practical philosophy of philanthropy for the most pressing social causes which has grown into a gigantic industry-cum-fad of the global capitalist elites. This article presents a critique of EA, EA-adjacent practices of Islamic philanthropy, and alternative economic proposals for rural welfare. To do so, this article uses insights from critical studies of political thought, critical political economy, and solidarity economy literature as an analytical lens in analyzing EA and Islamic philanthropy and formulating a synthesis of Islamic economic ethics and alter-capitalist rural welfare practices and institutions. This paper concludes that Islamic philanthropy and EA have serious limitations in improving rural welfare, especially in Global South countries such as Indonesia, and shows alternative pathways for agrarian justice.